The Integration of Digital Transformation in Educational Human Resource Management and Value Education: A Perspective from Global Youth Talent Development and Online Courses - Yangweiwei, Yangweiwei; Barokah Isdaryanti (JOURNAL SAINS STUDENT RESEARCH, 2025)
From the perspective of human resource planning, this paper explores how global higher education institutions integrate value education into the recruitment, development, and online training of young talents under digital transformation. It examines current practices, challenges, and development strategies in this area. By combining international research on sustainable human resource management, employee performance, emotional intelligence, organizational commitment, and leadership, the study identifies common issues such as weak top-level planning, narrow evaluation systems, fragmented training processes, and insufficient welfare support for young academic staff. The research further shows that digital technologies such as virtual reality, artificial intelligence, and big data can overcome traditional time and space limits in education. These tools help achieve a three-dimensional goal of “knowledge transfer, skill development, and value formation.”he paper suggests that universities should strengthen the system and foresight of discipline planning, build multi-dimensional evaluation systems that value innovation and social contribution, establish full-cycle talent management mechanisms, and promote innovative use of digital technologies in value education.Finally, based on global best practices, this study provides strategic recommendations for higher education institutions in areas such as technology ethics, inter-university collaboration, and intelligent education development.